Pharmacists in primary healthcare: integration of pharmacy services into aboriginal communities / Mohd Shah Rezan Hamzah - Hamzah, Mohd Shah Rezan (Faculty of Pharmacy, 2024)
Integrating pharmacy services into Aboriginal communities has been transformative in the Kuala Langat District, particularly through implementing mobile clinic services. These clinics serve 11 aboriginal villages